Inter-Hospital Transportation of Patients on Extracorporeal Life Support: A Single Center Experience - Yang Hyun Cho (Korean Journal of Critical Care Medicine, 2014)
Background: Extracorporeal life support (ECLS) is an effective life-saving tool for patients in refractory cardiac or respiratory failure. Although transportation of patients on ECLS is challenging, it is necessary in some instances. We report our initial experience of transporting patients on ECLS. Methods: The study period was between January 2004 and August 2013. We reviewed our ECLS database and identified four patients who were transported to our institution on ECLS. We excluded patients who were not transported by our ECLS team. Results: There were no clinically significant events during transportation. ECLS indications included acute respiratory distress syndrome in two patients, stress-induced cardiomyopathy induced by pneumonia sepsis in one patient, and cardiac arrest caused by amyloid cardiomyopathy in another patient. One patient was transported by helicopter and three patients were transported in an oversized ambulance. Three patients were successfully weaned off ECLS and discharged without significant complications. Conclusions: Inter-hospital transport can be safely performed by an experienced ECLS team. Successful transport may improve patient outcome and the ECLS programs of both referring and referral hospitals.